# Is there a teacher in the house?

Printable View

• Apr 6th 2009, 04:02 PM
inthebegining
Is there a teacher in the house?
If so if u have time can u check my work i think i got most of these problems right just wanted to check ur help will help me have a better life in the future

2. Simplify and combine like terms:
(1/4)(3x - 2) - (5/4)(2x - 6)
(1/4)-(5/4)=(4/4)=1
(3x – 2)- -2x +6=
5x -8

3. Solve for x, collect variables on the left side of the equation:
7x - 3 = - 5x – 18
7x + 5x =12x -5x +5x =0
12x -3+3 =-18+3
Divide 12 both sides 12/12x=-15/12
X=-4/3 x=-1 1/3

4. Solve for x, collect variables on the left side of the equation:
4(x - 3) + 2 = 3x + 8 - 2x
4x -12 +2 = 3x +8 -2x
3x-2x=x -12 + 2=-10
4x -10=x+8
-x from both sides 3x -10=8
Add 10 both sides 3x=18
Divide 3 both sides x=6

5. Solve for x, collect variables on the left side of the equation:
(x – 4)/2 – 1/4 = (6x - 1)/20
Find LCD and simplify x -4 – 1/2 = 6x-1/10 add 1 to each side
10 times all terms 10x – 30 - 5 = 60x
Minus 10x form both sides -25 = 50x
Dived
• Apr 6th 2009, 04:54 PM
Prove It
Quote:

Originally Posted by inthebegining
If so if u have time can u check my work i think i got most of these problems right just wanted to check ur help will help me have a better life in the future

2. Simplify and combine like terms:
(1/4)(3x - 2) - (5/4)(2x - 6)
(1/4)-(5/4)=(4/4)=1
(3x – 2)- -2x +6=
5x -8

3. Solve for x, collect variables on the left side of the equation:
7x - 3 = - 5x – 18
7x + 5x =12x -5x +5x =0
12x -3+3 =-18+3
Divide 12 both sides 12/12x=-15/12
X=-4/3 x=-1 1/3

4. Solve for x, collect variables on the left side of the equation:
4(x - 3) + 2 = 3x + 8 - 2x
4x -12 +2 = 3x +8 -2x
3x-2x=x -12 + 2=-10
4x -10=x+8
-x from both sides 3x -10=8
Add 10 both sides 3x=18
Divide 3 both sides x=6

5. Solve for x, collect variables on the left side of the equation:
(x – 4)/2 – 1/4 = (6x - 1)/20
Find LCD and simplify x -4 – 1/2 = 6x-1/10 add 1 to each side
10 times all terms 10x – 30 - 5 = 60x
Minus 10x form both sides -25 = 50x
Dived

2. $\frac{1}{4}(3x - 2) - \frac{5}{4}(2x - 6)$.

You can only do the $\frac{1}{4} - \frac{5}{4}$ if you have a common factor. Here you don't.

So you expand instead.

$\frac{1}{4}(3x - 2) - \frac{5}{4}(2x - 6) = \frac{3}{4}x - \frac{1}{2} - \frac{5}{2}x + \frac{15}{2}$

Now collect the like terms

$= -\frac{7}{4}x + 7$.

3. $7x - 3 = -5x - 18$

Collect all the x terms on one side and the constants on the other.

$7x + 5x = -18 + 3$

$12x = -15$

$x = -\frac{15}{12}$

$x = -\frac{5}{4}$.

4. $4(x - 3) + 2 = 3x + 8 - 2x$

$4x - 12 + 2 = x + 8$

$4x - 10 = x + 8$

$4x - x = 8 + 10$

$3x = 18$

$x = 6$.

5. $\frac{x - 4}{2} - \frac{1}{4} = \frac{6x - 1}{20}$

We need to get rid of the denominators. Do this by multiplying both sides by 20 (since 2 and 4 are also factors of 20)

$\frac{20(x - 4)}{2} - \frac{20}{4} = 6x - 1$

$10(x - 4) - 5 = 6x - 1$

$10x - 40 - 5 = 6x - 1$

$10x - 45 = 6x - 1$

$10x - 6x = -1 + 45$

$4x = 44$

$x = 11$.